Analysis of power transmission through IOL with glistenings and whitenings by T-Matrix. (September 2020) - Min Han, Kay Thwe; Kazunori, Kotani; Siritanawan, Prarinya; Kongprawechnon, Waree; Sinthanayothin, Chanjira
Highlights: Effect of glistening characteristics on intraocular lens transmission in the eyes is analyzed from electrical point of view. Light transmission through IOL with glistenings are calculated. Multiple light scattering of glistenings and whitenings are applied by T-Matrix. Light scattering simulation software, CELES (CUDA-accelerated simulation of electromagnetic scattering) is applied and studied the light transmission. Abstract: Light transmission through Intraocular lens (IOL) with glistenings and whitenings are analyzed by using T-matrix theory. Visual function is decreased due to glistening and subsurface nanoglistening (whitening). Glistening means fluid-filled micro-sized vacuoles, on the other hand, whitening is nano-sized vacuoles in intraocular lens (IOL) which lead to light scattering and affect human's vision quality. Glistening observation and light scattering in IOL are observed from the characteristics of glistenings which are size, shape, refractive index and number of glistenings. When microvacuoles are densely located in IOL, light scattering for single particle is not sufficient and multiple light scattering is important to be considered. Therefore, the correlation between light transmission and glistening characteristics are investigated from electromagnetic scattering approach called T-matrix. For this purpose, light scattering simulation software, CELES (CUDA-accelerated simulation of electromagnetic scattering) is applied and studied the light transmission in terms of power reflectivity and transitivity. The simulation result can show that light transmittance through IOL to retina and evaluate the quality of the vision by light scattering.